Socialinė visuomenės informatizavimo problematika - Gudonienė, Vilija (Knygotyra, 1988)
The article is devoted to the problems of the impact of informatization on society. Some theories of the post-industrial information society are discussed. These theories are constructed on emphasizing the role of the influence of informatization on the social development of society. An attempt is made to trace the basic ideas of D. Bell’s, Y. Masuda’s, J. J. Servan-Schreiber’s, and A. Toffler’s theories of the information society. Some other empirical researches on the economic and social consequences of informatization are analyzed. The attention is paid to phenomena of the information industry, the social role of electronic communications, information technology and work, social limitations on the use, and political aspects of the new information technology, as well as the problems of the international transfer of information.